Nanocrystalline non-binding-phase hard alloy and preparation method and application thereof

By covering the metal layer on the surface of the presintered body, combining vacuum sintering and hot isostatic sintering, the contradiction between sintering densification and grain growth is solved, and the high density of nanocrystal non-bonded phase cemented carbide is achieved and Small grain size, suitable for mass production.

CN119287197AActive Publication Date: 2025-01-10XIAMEN TUNGSTEN CO LTD +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411417217.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

In the prior art, higher temperatures promote sintering densification but lead to grain growth, which is inconsistent with the fact that lower temperatures suppress grain growth but not sintering is not dense, and it is difficult to achieve sintering densification under the condition of controlling the grain size, and Meet mass production needs.

Method used

The surface of the presintered body is coated with at least two metal layers, and a dense metal sealing layer is formed by vacuum sintering, and then thermal isostatic sintering is performed at a lower temperature to prevent high-pressure gas from entering and uniformly transfer pressure, achieving non-adhesive nanocrystalline stickiness at a lower temperature. Densification of junction cemented carbide.

Benefits of technology

Sintering density of the non-bonded phase cemented carbide is achieved at a lower temperature, and nanocrystalline carbide with an average grain size of less than 200 nm and a relative density of more than 99.8%, and vacuum sintering and thermal isostatic sintering are not subject to vacuum sintering and thermal isostatic sintering. Product shape is limited and suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287197A_ABST
    Figure CN119287197A_ABST
Patent Text Reader

Abstract

The invention provides a nanocrystalline unbonded hard alloy and a preparation method and application thereof, and the preparation method comprises the following steps: coating at least two metal layers on the surface of a pre-sintered body, and then sequentially carrying out vacuum sintering and hot isostatic pressing sintering to obtain the nanocrystalline unbonded hard alloy, the relative density of the pre-sintered body is 80% to 92%, and the average crystal grain size of the pre-sintered body is 150 nm or less; according to the method, the surface of the pre-sintered body is coated with the at least two metal layers, sintering densification of the binding-phase-free hard alloy at the low temperature is achieved, and therefore the contradiction that sintering densification is promoted at the high temperature, but grain growth is caused, and grain growth is inhibited at the low temperature, but sintering is not densified is solved; and finally, the nanocrystalline binding-phase-free hard alloy with the average grain size being smaller than 200 nm and the relative density being higher than 99.8% can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cemented carbide, and relates to a cemented carbide and a preparation method and application thereof, and in particular to a nanocrystalline binderless cemented carbide and a preparation method and application thereof. Background Art

[0002] Binderless cemented carbide refers to a WC-based cemented carbide with WC as the main hard phase and a total binder phase content of no more than 1wt% composed of binder phase metals such as Co, Ni or Fe. Due to the extremely low binder phase content, compared with traditional cemented carbide, binderless cemented carbide has excellent wear resistance, oxidation resistance, corrosion resistance and polishing properties. Therefore, it is widely used in wear-resistant fields such as super-mirror glass lens molds, cutting tools, and water jet sand pipes.

[0003] Generally, as the grain size decreases, the toughness of cemented carbide increases at the same time. According to the "Grain Size Classification Standard for Cemented Carbide", cemented carbide with an average grain size of less than 200nm in the hard phase is generally called nanocrystalline cemented carbide. In order to improve the toughness and polishability of cemented carbide without a binder phase, it is necessary to reduce the grain size of the hard phase.

[0004] The addition of grain inhibitors can effectively inhibit the grain growth of the hard phase, but the addition of grain inhibitors will have an adverse effect on the performance of cemented carbide; however, if the amount of grain inhibitor added is reduced, the effect of inhibiting grain growth will be affected.

[0005] Lowering the sintering temperature and shortening the sintering time can also inhibit the growth of hard phase grains, but it is easy to cause the problem of non-dense sintering. In order to achieve the purpose of inhibiting grain growth and sintering densely, the prior art CN107522490A adopts hot pressing sintering (HP), CN103667845A adopts high temperature and high pressure sintering (HTHP), CN102925728A and CN108165859A adopt spark plasma sintering (SPS). The above methods assist external pressure during sintering, which is beneficial to improve sintering density. At the same time, the sintering temperature and sintering time can also be appropriately reduced and reduced, which is beneficial to inhibit grain growth; however, the production efficiency of the above methods is low; and the biggest drawback of the above methods is that they can only produce products with relatively simple shapes, and the product size is limited; the high pressure oscillation assisted sintering (OPS) disclosed in CN110171975A and CN115125426A also has the above problems.

[0006] The hot isostatic pressing (HIP) method disclosed in the prior art such as CN113897506A uses gas pressure to pressurize and sinter the product. It is not limited by the shape of the product, can achieve mass production, and can also promote sintering densification at a relatively low temperature. However, before HIP sintering, the pre-sintered body needs to have a relative density of more than 93%, that is, it is necessary to ensure that the interior of the pre-sintered body is a closed gap, so as to prevent high-pressure gas from entering the interior of the pre-sintered body during HIP sintering to ensure sintering density. However, when the pre-sintered body has a relative density of more than 93%, it is necessary to increase the sintering temperature of the pre-sintered body, resulting in grain growth.

[0007] It can be seen from this that the existing technology has a contradiction that higher temperature promotes sintering densification but causes grain growth, and lower temperature inhibits grain growth but the sintering is not dense. How to achieve sintering densification under the condition of controlling grain size and meet the needs of mass production of products is a problem that needs to be urgently solved in this field. Summary of the invention

[0008] The purpose of the present invention is to provide a nanocrystalline binderless cemented carbide and a preparation method and application thereof, so as to solve the contradiction in the prior art that higher temperature promotes sintering densification but causes grain growth, and lower temperature inhibits grain growth but sintering is not dense, thereby obtaining a dense nanocrystalline binderless cemented carbide.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a nanocrystalline binderless cemented carbide, the preparation method comprising the following steps:

[0011] Coating at least two metal layers on the surface of the pre-sintered body, and then sequentially performing vacuum sintering and hot isostatic pressing sintering to obtain the nanocrystalline binder-free cemented carbide;

[0012] The relative density of the pre-sintered body is 80% to 92%, and the average grain size of the pre-sintered body is less than 150nm;

[0013] The melting point of the outermost metal layer of the at least two metal layers is T m2 Higher than the melting point T of the innermost metal layer m1 And the vacuum sintering temperature T 1 ;

[0014] The melting point of the innermost metal layer is T m1 Than the vacuum sintering temperature T 1 Low 0℃ to 20℃;

[0015] The melting point of each of the at least two metal layers is higher than the hot isostatic pressing sintering temperature T2 .

[0016] The preparation method provided by the present invention covers at least two metal layers on the surface of a pre-sintered body, melts the innermost metal layer through vacuum sintering, forms a dense metal sealing layer on the surface of the pre-sintered body, and then performs hot isostatic pressing sintering at a relatively low temperature below the melting point of the innermost metal layer, thereby maintaining the innermost metal layer in a solid state and good plasticity, not only preventing high-pressure gas from entering the pre-sintered body, but also transmitting the pressure to the pre-sintered body evenly and well, thereby ensuring the densification of the nanocrystalline binderless cemented carbide, and effectively inhibiting grain growth. That is, by coating the surface of the pre-sintered body with at least two metal layers, the binderless cemented carbide can be sintered densely at a relatively low temperature, thereby solving the contradiction between higher temperature promoting sintering densification but causing grain growth and lower temperature inhibiting grain growth but sintering not being dense. Finally, a nanocrystalline binderless cemented carbide with an average grain size of less than 200nm and a relative density of more than 99.8% can be obtained. In addition, vacuum sintering and hot isostatic pressing sintering are not limited by product shape and can achieve mass production.

[0017] The present invention does not specifically limit the specific shape and preparation method of the pre-sintered body, as long as its relative density is between 80% and 92% and the average grain size is not greater than 150nm. The relative density of the pre-sintered body refers to the ratio of the density of the pre-sintered body to the theoretical density of nanocrystalline cemented carbide without binder phase.

[0018] The innermost metal layer of the present invention refers to the metal layer closest to the pre-sintered body among at least two metal layers; the outermost metal layer refers to the metal layer farthest from the pre-sintered body among at least two metal layers.

[0019] Preferably, the melting point of the innermost metal layer is m1 1430℃ to 1820℃.

[0020] Preferably, the material of the innermost metal layer includes any one of Ni, Co, Fe or Ti or a combination of at least two of them, or a combination of Zr and at least one of Ni, Co, Fe or Ti.

[0021] Preferably, the material of the outermost metal layer includes any one of Ti, Zr, Mo, Nb or Ta, or a combination of at least two of them.

[0022] Preferably, the thickness of the innermost metal layer is 0.1 mm to 0.5 mm.

[0023] Preferably, the thickness of the outermost metal layer is 0.1 mm to 0.3 mm.

[0024] Preferably, the vacuum sintering is performed in a high vacuum.

[0025] Preferably, the vacuum sintering temperature T 1 1430℃ to 1840℃.

[0026] Preferably, the holding time of the vacuum sintering is 0.5h to 1h.

[0027] Preferably, the vacuum sintering pressure is 10 -3 Below Pa.

[0028] Preferably, the hot isostatic pressing sintering is performed in an inert atmosphere.

[0029] Preferably, the hot isostatic pressing sintering pressure is 150 MPa to 300 MPa.

[0030] Preferably, the melting point of the innermost metal layer is m1 Than the hot isostatic pressing temperature T 2 10℃ to 50℃ higher.

[0031] Preferably, the hot isostatic pressing sintering temperature T 2 1380℃ to 1810℃.

[0032] Preferably, the holding time of the hot isostatic pressing sintering is 1 h to 3 h.

[0033] Preferably, the method for preparing the pre-sintered body comprises powder mixing, molding, degreasing and vacuum pre-sintering performed in sequence.

[0034] Preferably, the vacuum pre-sintering temperature T 3 1450℃ to 1870℃.

[0035] Preferably, the holding time of the vacuum pre-sintering is 1 h to 3 h.

[0036] Preferably, the vacuum pre-sintering pressure is below 30 Pa.

[0037] Preferably, the composition of the nanocrystalline binder-free cemented carbide includes, by mass percentage, more than 91 wt % of WC, less than 1 wt % of a binder metal, and the remainder of additives.

[0038] Preferably, the bonding phase metal includes any one of Co, Ni or Fe, or a combination of at least two of them.

[0039] Preferably, the additive includes Cr 3 C 2 、VC、ZrC、TiC、Mo 2 C, TaC, NbC, SiC, B4C, ZrB, ZrB 2, TiB, TiB 2 , WB, W 2 B.W 2 B 5 , CrB, AlN, ZrN, TiN, TiCN, Si 3 N 4 , BN or rare earth metals, any one or a combination of at least two.

[0040] In a second aspect, the present invention provides a nanocrystalline binderless cemented carbide, wherein the nanocrystalline binderless cemented carbide is prepared by the preparation method described in the first aspect;

[0041] The average grain size of the nanocrystalline binder-free hard alloy is less than 200 nm, and the relative density is higher than 99.8%.

[0042] In a third aspect, the present invention provides an application of a nanocrystalline cemented carbide without a binder phase, wherein the nanocrystalline cemented carbide without a binder phase is used to prepare molds, cutting tools or wear-resistant parts;

[0043] The nanocrystalline binder-free cemented carbide is prepared by the preparation method described in the first aspect, or is the nanocrystalline binder-free cemented carbide described in the second aspect.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] (1) The present invention realizes the sintering of binderless cemented carbide at a relatively low temperature by coating at least two metal layers on the surface of the pre-sintered body, thereby resolving the contradiction between high temperature promoting sintering densification but causing grain growth and low temperature inhibiting grain growth but not sintering densification. Finally, a nanocrystalline binderless cemented carbide with an average grain size of less than 200 nm and a relative density of more than 99.8% can be obtained. In addition, vacuum sintering and hot isostatic pressing sintering are not limited by product shape and can achieve mass production.

[0046] (2) The average grain size of the nanocrystalline binder-free cemented carbide prepared by the present invention is less than 200 nm, and the relative density is higher than 99.8%. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a fracture morphology of the nanocrystalline binder-free cemented carbide obtained in Example 1 of the present invention;

[0048] Figure 2 This is a grain morphology image of the polished and corroded surface of the nanocrystalline binder-free cemented carbide obtained in Example 1 of the present invention;

[0049] Figure 3 This is a fracture morphology of a cemented carbide without a binder phase obtained in Comparative Example 2 of the present invention;

[0050] Figure 4 This is a grain morphology image of the polished and corroded surface of the binder-free cemented carbide obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] A certain embodiment of the present invention provides a method for preparing a nanocrystalline binderless cemented carbide, the preparation method comprising the following steps:

[0053] Coating at least two metal layers on the surface of the pre-sintered body, and then sequentially performing vacuum sintering and hot isostatic pressing sintering to obtain the nanocrystalline binder-free cemented carbide;

[0054] The relative density of the pre-sintered body is 80% to 92%, and the average grain size of the pre-sintered body is less than 150nm;

[0055] The melting point of the outermost metal layer of the at least two metal layers is T m2 Higher than the melting point T of the innermost metal layer m1 And the vacuum sintering temperature T 1 ;

[0056] The melting point of the innermost metal layer is T m1 Than the vacuum sintering temperature T 1 Low 0℃ to 20℃;

[0057] The melting point of each of the at least two metal layers is higher than the hot isostatic pressing sintering temperature T 2 .

[0058] The preparation method provided by the present invention covers at least two metal layers on the surface of a pre-sintered body, melts the innermost metal layer through vacuum sintering, forms a dense metal sealing layer on the surface of the pre-sintered body, and then performs hot isostatic pressing sintering at a relatively low temperature below the melting point of the innermost metal layer, thereby maintaining the innermost metal layer in a solid state and good plasticity, not only preventing high-pressure gas from entering the pre-sintered body, but also transmitting the pressure to the pre-sintered body evenly and well, thereby ensuring the densification of the nanocrystalline binderless cemented carbide, and effectively inhibiting grain growth. That is, by coating the surface of the pre-sintered body with at least two metal layers, the binderless cemented carbide can be sintered densely at a relatively low temperature, thereby solving the contradiction between higher temperature promoting sintering densification but causing grain growth and lower temperature inhibiting grain growth but sintering not being dense. Finally, a nanocrystalline binderless cemented carbide with an average grain size of less than 200nm and a relative density of more than 99.8% can be obtained. In addition, vacuum sintering and hot isostatic pressing sintering are not limited by product shape and can achieve mass production.

[0059] The present invention does not specifically limit the specific shape and preparation method of the pre-sintered body, as long as its relative density is between 80% and 92% and the average grain size is below 150nm. The relative density of the pre-sintered body refers to the ratio of the density of the pre-sintered body to the theoretical density of nanocrystalline cemented carbide without binder phase.

[0060] The innermost metal layer of the present invention refers to the metal layer closest to the pre-sintered body among at least two metal layers; the outermost metal layer refers to the metal layer farthest from the pre-sintered body among at least two metal layers.

[0061] In order to obtain a nanocrystalline binderless cemented carbide having an average grain size of less than 200 nm and a relative density higher than 99.8%, in the preparation method provided by the present invention, when the average grain size of the pre-sintered body is less than 150 nm, it is necessary to make its relative density 80% to 92%, for example, it can be 80%, 85%, 90% or 92%, but is not limited to the listed values, and the remaining values ​​not listed in the numerical range are also applicable.

[0062] In some embodiments, the melting point of the innermost metal layer is m1 It is 1430°C to 1820°C, for example, it can be 1430°C, 1500°C, 1600°C, 1700°C, 1800°C or 1820°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] The material of the innermost metal layer of the present invention includes a single metal or an alloy composed of at least two metals. No matter what the material is, as long as its melting point T m1It is sufficient to meet the numerical range of 1430° C. to 1820° C. As a preferred technical solution, in order to facilitate at least two metal layers to cover the pre-sintered body of any shape, the material of the at least two metal layers has good room temperature plasticity.

[0064] In some embodiments, the material of the innermost metal layer includes any one or a combination of at least two of Ni (melting point 1455°C), Co (melting point 1495°C), Fe (melting point 1538°C) or Ti (melting point 1668°C), or a combination of Zr (melting point 1852°C) and at least one of Ni, Co, Fe or Ti, wherein the combination includes a simple mixture of at least two metals, or an alloy of at least two metal elements.

[0065] Exemplarily, when the material of the innermost metal layer includes any one of Ni, Co, Fe or Ti or a combination of at least two of them, typical but non-limiting combinations include a combination of Ni and Co, a combination of Co and Fe, a combination of Fe and Ti, a combination of Ni, Co and Fe, or a combination of Ni, Co, Fe and Ti.

[0066] Exemplarily, when the material of the innermost metal layer includes a combination of Zr and at least one of Ni, Co, Fe or Ti, typical but non-limiting combinations include a combination of Zr and Ni, a combination of Zr and Co, a combination of Zr and Fe, a combination of Zr and Ti, a combination of Zr, Ni and Co, a combination of Zr, Co and Fe, or a combination of Zr, Ni, Co, Fe and Ti.

[0067] In the preparation method provided by the present invention, the melting point of the outermost metal layer is T m2 Higher than the melting point T of the innermost metal layer m1 , and the melting point of the outermost metal layer is T m2 Higher than the vacuum sintering temperature T 1 , so that the outermost metal layer always remains solid during the entire preparation method, thereby preventing the remaining metal layers from being lost due to gravity during vacuum sintering and hot isostatic pressing, and ensuring the complete covering effect of the inner metal layer on the pre-sintered body.

[0068] In some embodiments, the material of the outermost metal layer includes any one of Ti (melting point 1668°C), Zr (melting point 1852°C), Mo (melting point 2623°C), Nb (melting point 2468°C) or Ta (melting point 2996°C), or a combination of at least two of them. Typical but non-limiting combinations include a combination of Ti and Zr, a combination of Zr and Mo, a combination of Mo and Nb, a combination of Nb and Ta, a combination of Ti, Zr, Mo and Nb, a combination of Zr, Mo, Nb and Ta, or a combination of Ti, Zr, Mo, Nb and Ta, wherein the combination includes a simple mixture of at least two metals, or an alloy including at least two metal elements.

[0069] The method of coating the surface of the pre-sintered body with at least two metal layers in the present invention is a conventional coating method, as long as the metal layers can form a non-airtight coating on the surface of the pre-sintered body.

[0070] Exemplarily, the method of coating the innermost metal layer on the surface of the pre-sintered body includes spraying or metal thin-walled part casing.

[0071] In some embodiments, when coating the innermost metal layer, the spraying method includes: uniformly spraying a slurry containing coating metal powder on the surface of the pre-sintered body, and forming the innermost metal coating layer after drying.

[0072] In certain embodiments, when coating the innermost metal layer, the method of sleeve installation of the metal thin-walled parts includes: preparing the metal to be coated into multiple thin-walled parts that are consistent with the appearance of the pre-sintered body, the multiple thin-walled parts are combined and sleeved and tightly attached to the surface of the pre-sintered body, and the interfaces of the multiple thin-walled parts are connected by nesting to form the innermost metal coating layer.

[0073] Exemplarily, the method of coating the outermost metal layer includes sleeve coating of a thin-walled metal member.

[0074] In certain embodiments, when coating the outermost metal layer, the method of sleeve installation of the metal thin-walled parts includes: preparing the metal to be coated into multiple thin-walled parts that are consistent with the appearance of the pre-sintered body that has been coated with the inner metal layer, the multiple thin-walled parts are combined and sleeved and tightly attached to the outer surface of the pre-sintered body that has been coated with the inner metal layer, and the interfaces of the multiple thin-walled parts are connected by nesting to form the outermost metal coating layer.

[0075] The present invention uses at least two metal layers to coat the pre-sintered body, wherein the thickness of the innermost metal layer is too thin, which will lead to insufficient melting and sealing of the innermost metal layer during subsequent vacuum sintering, and easily lead to diffusion of high-pressure gas into the pre-sintered body during hot isostatic pressing sintering, resulting in loose sintering, but too thick will lead to higher processing costs; wherein the thickness of the outermost metal layer is too thin, which will reduce the protective effect, and at the same time, since the metal layer needs to be removed by subsequent processing, too thick will also lead to higher processing costs. Therefore, in order to achieve a good protective effect, it is necessary to optimize the thickness of the innermost metal layer and the thickness of the outermost metal layer.

[0076] In some embodiments, the thickness of the innermost metal layer is 0.1 mm to 0.5 mm, for example, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm or 0.5 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0077] In some embodiments, the thickness of the outermost metal layer is 0.1 mm to 0.3 mm, for example, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm or 0.3 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0078] The total thickness of the at least two metal layers is related to the number of metal layers. The present invention only needs to control the thickness of the innermost metal layer and the thickness of the outermost metal layer. Exemplarily, the total thickness of the at least two metal layers is 0.2 mm to 1 mm, for example, it can be 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm, or 1 mm, but is not limited to the listed values, and the remaining values ​​not listed in the numerical range are also applicable.

[0079] In the present invention, during vacuum sintering, the vacuum sintering temperature T 1 Must be greater than or equal to the melting point T of the innermost metal layer m1 , that is, the innermost metal layer needs to be melted so that the pre-sintered body can be completely sealed; but the grains of the pre-sintered body need to be prevented from growing further, so the temperature of vacuum sintering cannot be too high; in addition, before the innermost metal layer is melted and sealed, various reactions that are easy to form gases in the pre-sintered body must be completed (water vapor and carbon and oxygen reactions, etc.), otherwise these gases cannot be discharged out of the pre-sintered body and are sealed in the sintered body to form pores, resulting in the inability to eliminate the above pores by hot isostatic pressing sintering, which deteriorates the performance of the final product. Therefore, it is necessary to optimize the temperature of vacuum sintering.

[0080] In some embodiments, the vacuum sintering temperature T 1It is 1430°C to 1840°C, for example, it can be 1430°C, 1450°C, 1500°C, 1600°C, 1700°C, 1800°C or 1840°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0081] In some embodiments, the holding time of the vacuum sintering is 0.5h to 1h, for example, it can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h or 1h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0082] In some embodiments, the vacuum sintering pressure is 10 -3 Pa or less to avoid the gases generated by the reaction being sealed in the pre-sintered body.

[0083] In certain embodiments, the hot isostatic pressing sintering is performed in an inert atmosphere.

[0084] The gas used in the inert atmosphere includes inert gases such as nitrogen and / or argon.

[0085] In some embodiments, the hot isostatic pressing sintering pressure is 150 MPa to 300 MPa, for example, 150 MPa, 180 MPa, 200 MPa, 240 MPa, 250 MPa, 280 MPa or 300 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0086] Under the condition of satisfying the relative density of the obtained nanocrystalline binder-free cemented carbide, the lower the hot isostatic pressing sintering temperature, the more conducive it is to inhibiting grain growth.

[0087] In some embodiments, the melting point of the innermost metal layer is m1 Than the hot isostatic pressing temperature T 2 10°C to 50°C higher, for example, 10°C, 20°C, 30°C, 40°C or 50°C, but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] In some embodiments, the hot isostatic pressing temperature T 2 It is 1380°C to 1810°C, for example, it can be 1380°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C or 1810°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0089] The melting point of the innermost metal layer is T m1 Specific heat isostatic pressing sintering temperature T 2The temperature is 10°C to 50°C higher. Within this temperature range, during hot isostatic pressing, the innermost metal layer remains in a solid sealed state, reducing the diffusion ability of the innermost metal layer under high pressure and further preventing the high-pressure gas from diffusing into the pre-sintered body. Moreover, within this temperature range, it can maintain good plasticity, thereby ensuring that the pressure of hot isostatic pressing can be effectively transmitted to the pre-sintered body, promoting its densification.

[0090] In some embodiments, the holding time of the hot isostatic pressing sintering is 1 h to 3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0091] In some embodiments, the method for preparing the pre-sintered body comprises powder mixing, molding, degreasing and vacuum pre-sintering in sequence.

[0092] In some embodiments, the mixed powder is prepared by configuring raw material powder according to the composition of nanocrystalline binderless cemented carbide, and performing ball milling to mix the raw material powder to obtain a uniformly mixed powder.

[0093] In some embodiments, the ball milling mixing includes: placing the formulated amount of each raw material powder in a ball mill, injecting anhydrous ethanol into the ball mill, and ball milling mixing in a protective atmosphere for more than 48 hours to obtain a uniformly mixed mixed powder with an average particle size of no more than 120nm.

[0094] In some embodiments, the grinding balls used in the ball milling mixture are carbide balls, and the mass ratio of the grinding balls to the raw material powder is 3:1 to 5:1, for example, it can be 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, but is not limited to the listed values, and the remaining unlisted values ​​within the numerical range are also applicable.

[0095] In some embodiments, the molding includes at least one of molding, cold isostatic pressing, extrusion molding, injection molding or 3D printing. The present invention does not specifically limit the molding method, as long as a molded body of a desired shape can be obtained. When the desired shape cannot be obtained by one-step molding, the molding can also include cutting.

[0096] In certain embodiments, the degreasing is inert gas negative pressure degreasing or hydrogen positive pressure degreasing.

[0097] In the present invention, in order to obtain a pre-sintered body with a relative density of 80% to 92% and an average grain size of less than 150nm, the vacuum pre-sintering temperature T 3It is crucial. If the temperature of vacuum pre-sintering is too low, the grains of the obtained pre-sintered body will not grow excessively, and the grain size will be relatively small, but the relative density of the pre-sintered body will be less than 80%, and there will be more pores, resulting in lower strength of the pre-sintered body. It will lead to the following two unfavorable results: (1) Due to the low strength of the pre-sintered body, it is not conducive to the operation of coating the metal layer on its surface, which is easy to damage the pre-sintered body; (2) Due to the large number of pores, during the subsequent vacuum sintering, the metal liquid phase formed after the innermost metal layer is melted is easy to diffuse along the pores to the interior of the pre-sintered body, resulting in excessive diffusion depth, thereby affecting the surface quality of the final nanocrystalline binderless cemented carbide; if the temperature of vacuum pre-sintering is too high, although the relative density of the pre-sintered body can be increased, nano-sized grains cannot be obtained.

[0098] In some embodiments, the vacuum pre-sintering temperature T 3 It is 1450°C to 1870°C, for example, it can be 1450°C, 1500°C, 1600°C, 1700°C, 1800°C, 1850°C or 1870°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0099] In some embodiments, the holding time of the vacuum pre-sintering is 1 h to 3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0100] In some embodiments, the vacuum pre-sintering pressure is below 30 Pa.

[0101] In certain embodiments, the composition of the nanocrystalline binder-free cemented carbide includes, by weight percentage, more than 91 wt % of WC, less than 1 wt % of a binder metal, and the balance of additives.

[0102] In certain embodiments, the binder phase metal includes any one of Co, Ni or Fe or a combination of at least two of them, and typical but non-limiting combinations include a combination of Co and Ni, a combination of Co and Fe, a combination of Ni and Fe, or a combination of Co, Ni and Fe. The combination includes a simple physical mixture of the binder phase metals, or an alloy consisting of at least two metals.

[0103] In certain embodiments, the additive includes Cr 3 C 2 、VC、ZrC、TiC、Mo 2 C, TaC, NbC, SiC, B4C, ZrB, ZrB 2 , TiB, TiB 2 , WB, W 2 B.W 2 B5 , CrB, AlN, ZrN, TiN, TiCN, Si 3 N 4 , BN or rare earth metals, any one or a combination of at least two.

[0104] A certain embodiment of the present invention provides a nanocrystalline cemented carbide without a binder phase, wherein the nanocrystalline cemented carbide without a binder phase is prepared by the preparation method described in any embodiment;

[0105] The average grain size of the nanocrystalline binder-free hard alloy is less than 200 nm, and the relative density is higher than 99.8%.

[0106] A certain embodiment of the present invention provides an application of a nanocrystalline binderless cemented carbide, wherein the nanocrystalline binderless cemented carbide is used to prepare molds, cutting tools or wear-resistant parts;

[0107] The nanocrystalline binderless cemented carbide is prepared by the preparation method described in any embodiment, or is the nanocrystalline binderless cemented carbide described in any embodiment.

[0108] Pre-sintered body preparation

[0109] Preparation Example 1

[0110] This preparation example provides a method for preparing a pre-sintered body. In terms of mass percentage, the raw material powder of the pre-sintered body includes 99wt% WC, 0.2wt% Co, 0.5wt% Cr 3 C 2 and 0.3wt% VC, the preparation method comprises the following steps:

[0111] (1) In a nitrogen atmosphere, the raw material powder is placed in a ball mill and ball-milled for 72 hours, with the mass ratio of grinding balls to raw material powder being 4:1, so that the average particle size of the obtained mixed powder is less than 120 nm;

[0112] (2) cold isostatic pressing at a pressure of 200 MPa to obtain a molded body;

[0113] (3) performing a first degreasing stage, a second degreasing stage, a third degreasing stage and a fourth degreasing stage in sequence; wherein the first degreasing stage, the second degreasing stage and the third degreasing stage are performed in an argon atmosphere and under a degreasing pressure of 400 Pa:

[0114] First degreasing stage: over 3 hours, the temperature is evenly raised from room temperature to 120°C;

[0115] Second degreasing stage: After 6 hours, the temperature is evenly increased from 120℃ to 360℃;

[0116] The third degreasing stage: 360℃ for 3h;

[0117] Fourth degreasing stage: stop filling with argon, evacuate to a pressure below 30Pa, and evenly increase the temperature from 360°C to 650°C, and keep warm for 1h;

[0118] (4) Under the condition of pressure below 30Pa, at T 3 The pre-sintered body was vacuum pre-sintered at a temperature of 1700°C for 2 hours to obtain a pre-sintered body with a relative density of 86%.

[0119] In Preparation Examples 2 to 3 and Comparative Preparation Examples 1 and 2 shown in Table 1, except that the parameter conditions of vacuum pre-sintering are different from those of Preparation Example 1, the rest are the same as Preparation Example 1.

[0120] Table 1. Vacuum pre-sintering process parameters of preparation examples and comparative preparation examples and structural parameters of the obtained pre-sintered bodies

[0121]

[0122] Preparation Example 4

[0123] This preparation example provides a method for preparing a pre-sintered body. In terms of mass percentage, the raw material powder of the pre-sintered body includes 99.5wt% WC, 0.3wt% Cr 3 C 2 and 0.2wt% VC;

[0124] In the preparation method, except for the vacuum pre-sintering temperature T 3 Except for the temperature being 1870°C, the rest is the same as Preparation Example 1.

[0125] The relative density of the pre-sintered body obtained in this preparation example is 92%, and the average grain size is 147 nm.

[0126] Preparation Example 5

[0127] This preparation example provides a method for preparing a pre-sintered body. In terms of mass percentage, the raw material powder of the pre-sintered body includes 96.3wt% WC, 0.2wt% Co, 2wt% TiC, 0.5wt% Cr 3 C 2 and 1 wt% TaC;

[0128] In the preparation method, except for the vacuum pre-sintering temperature T 3 Except for the temperature being 1530°C, the rest is the same as Preparation Example 1.

[0129] The relative density of the pre-sintered body obtained in this preparation example is 82%, and the average grain size is 113 nm.

[0130] Preparation Example 6

[0131] This preparation example provides a method for preparing a pre-sintered body. In terms of mass percentage, the raw material powder of the pre-sintered body includes 95.6wt% WC, 0.9wt% Co, 2wt% TiC, 0.5wt% Cr 3 C 2 and 1 wt% TaC;

[0132] In the preparation method, except for the vacuum pre-sintering temperature T 3 Except for the temperature being 1450°C, the rest is the same as Preparation Example 1.

[0133] The relative density of the pre-sintered body obtained in this preparation example is 80%, and the average grain size is 103 nm.

[0134] Example 1-1

[0135] This embodiment provides a method for preparing a nanocrystalline binderless cemented carbide, the preparation method comprising the following steps:

[0136] (a) Two metal layers are coated on the surface of the pre-sintered body; the material of the innermost metal layer is titanium (melting point T m1 1668℃), thickness 0.3mm; the material of the outermost metal layer is molybdenum (melting point T m2 2623℃), thickness is 0.2mm;

[0137] The coating method of the innermost metal layer is spray coating; the coating method of the outermost metal layer is metal thin-walled parts sleeve method;

[0138] The pre-sintered body is the pre-sintered body provided in Preparation Example 1;

[0139] (b) At a pressure of 10 -3 The vacuum sintering is carried out under the condition of less than Pa, and the vacuum sintering temperature T 1 The temperature is 1668℃ and the holding time is 1h;

[0140] (c) Hot isostatic pressing sintering was carried out in an argon atmosphere at a pressure of 170 MPa and a temperature of T 2 The temperature is 1640℃ and the holding time is 1.5h to obtain nanocrystalline cemented carbide without binder phase.

[0141] The fracture morphology of the nanocrystalline binderless cemented carbide obtained in this embodiment is as follows: Figure 1 As shown, the grain morphology of the polished and corroded surface is shown in Figure 2 As shown by Figure 1 and Figure 2 It can be seen that the nanocrystalline binder-free cemented carbide obtained in this embodiment is completely sintered and dense, with a relative density of 100%, and an average grain size of 170 nm.

[0142] Example 1-2

[0143] This embodiment provides a method for preparing nanocrystalline cemented carbide without a binder phase. 1 The temperature is 1688°C and the holding time is 0.5h, and the rest is the same as Example 1-1.

[0144] Compared with Example 1-1, since the vacuum sintering temperature is increased but the holding time is reduced, the nanocrystalline binderless cemented carbide obtained in this example is completely sintered and dense, with a relative density of 100%, and the average grain size is slightly increased to 177nm.

[0145] Examples 1-3

[0146] This embodiment provides a method for preparing nanocrystalline cemented carbide without a binder phase, except that the hot isostatic pressing temperature T 2 The temperature is 1658°C and the holding time is 1h, and the rest is the same as Example 1-1.

[0147] Compared with Example 1-1, the hot isostatic pressing sintering temperature is increased in this example, and the obtained nanocrystalline binderless cemented carbide is completely sintered and dense, with a relative density of 100%, and the average grain size is slightly increased to 173 nm.

[0148] Examples 1-4

[0149] This embodiment provides a method for preparing nanocrystalline cemented carbide without a binder phase, except that the hot isostatic pressing temperature T 2 The temperature is 1618°C and the holding time is 3h, and the rest is the same as Example 1-1.

[0150] Compared with Example 1-1, since the hot isostatic pressing sintering temperature is lowered and the holding time is increased in this example, the sintering density of the nanocrystalline binderless cemented carbide obtained in this example is slightly poor, and the relative density reaches 99.93%, but the average grain size is slightly reduced to 164nm.

[0151] Examples 1-5

[0152] This embodiment provides a method for preparing nanocrystalline cemented carbide without a binder phase, except that the hot isostatic pressing temperature T 2 Except for the temperature being 1600°C, the rest are the same as those in Example 1-1.

[0153] Compared with Examples 1-4, since the hot isostatic pressing sintering temperature is further reduced in this example, the density of the nanocrystalline binderless cemented carbide obtained in this example is further reduced, the relative density reaches 99.81%, and the average grain size is further reduced to 158nm.

[0154] Example 2

[0155] This embodiment provides a method for preparing nanocrystalline binderless cemented carbide. Except that the pre-sintered body is the pre-sintered body provided in Preparation Example 2, the rest is the same as that of Example 1-1.

[0156] Compared with Example 1-1, the relative density of the pre-sintered body in this example is reduced, resulting in a slight diffusion of the molten liquid phase on the surface of the pre-sintered body along the pores after the innermost metal layer melts during vacuum sintering, and the surface quality of the obtained nanocrystalline cemented carbide without a binder phase is slightly poor. However, due to the reduced temperature of vacuum pre-sintering, the average grain size of the pre-sintered body is finer. Under the subsequent vacuum sintering and hot isostatic pressing sintering process that is the same as that of Example 1-1, the obtained nanocrystalline cemented carbide without a binder phase is also completely dense, and the relative density reaches 100%; and due to the increase in pores, the distance for the mutual diffusion, migration and growth of the grains during sintering is relatively increased, thereby increasing the energy required for grain growth. Therefore, the average grain size of the obtained nanocrystalline cemented carbide without a binder phase is also finer than that of Example 1-1, reaching 152nm.

[0157] Example 3

[0158] This embodiment provides a method for preparing nanocrystalline binderless cemented carbide. Except that the pre-sintered body is the pre-sintered body provided in Preparation Example 3, the rest is the same as that of Example 1-1.

[0159] Compared with Example 1-1, the present embodiment provides a pre-sintered body by Preparation Example 3. It is obvious that due to the increase in vacuum pre-sintering temperature, the relative density of the pre-sintered body of Preparation Example 3 increases to 92%, and the grains grow further, with an average size of 146nm. Under the subsequent vacuum sintering and hot isostatic pressing sintering process identical to that of Example 1-1, the obtained nanocrystalline binderless cemented carbide is also fully dense, with a relative density of 100%, and an average grain size of 197nm.

[0160] Example 4

[0161] This embodiment provides a method for preparing a nanocrystalline binderless cemented carbide, the preparation method comprising the following steps:

[0162] (a) Two metal layers are coated on the surface of the pre-sintered body; the material of the innermost metal layer is zirconium-titanium alloy (melting point T m11820℃), thickness 0.3mm; the material of the outermost metal layer is molybdenum (melting point T m2 2623℃), thickness is 0.2mm;

[0163] The coating method of the innermost metal layer is spray coating; the coating method of the outermost metal layer is metal thin-walled parts sleeve method;

[0164] The pre-sintered body is the pre-sintered body provided in Preparation Example 4;

[0165] (b) At a pressure of 10 -3 The vacuum sintering is carried out under the condition of less than Pa, and the vacuum sintering temperature T 1 The temperature is 1820℃ and the holding time is 0.5h;

[0166] (c) Hot isostatic pressing sintering was carried out in an argon atmosphere at a pressure of 200 MPa and a temperature of T 2 The temperature is 1800℃ and the holding time is 1.5h to obtain nanocrystalline cemented carbide without binder phase.

[0167] The nanocrystalline binder-free cemented carbide obtained in this embodiment is completely sintered and dense, with a relative density of 100%, and an average grain size of 193 nm.

[0168] Example 5

[0169] This embodiment provides a method for preparing a nanocrystalline binderless cemented carbide, the preparation method comprising the following steps:

[0170] (a) Two metal layers are coated on the surface of the pre-sintered body; wherein the material of the innermost metal layer is cobalt (melting point T m1 1495℃), thickness 0.3mm; the material of the outermost metal layer is molybdenum (melting point T m2 2623℃), thickness is 0.2mm;

[0171] The coating method of the innermost metal layer is spray coating; the coating method of the outermost metal layer is metal thin-walled parts sleeve method;

[0172] The pre-sintered body is the pre-sintered body provided in Preparation Example 5;

[0173] (b) At a pressure of 10 -3 The vacuum sintering is carried out under the condition of less than Pa, and the vacuum sintering temperature T 1 The temperature is 1495℃ and the holding time is 0.5h;

[0174] (c) Hot isostatic pressing sintering was carried out in an argon atmosphere at a pressure of 200 MPa and a temperature of T 2 The temperature is 1460℃ and the holding time is 1.5h to obtain nanocrystalline cemented carbide without binder phase.

[0175] The nanocrystalline binder-free cemented carbide obtained in this example is completely sintered and dense, with a relative density of 100%, and an average grain size of 167 nm.

[0176] Example 6

[0177] This embodiment provides a method for preparing a nanocrystalline binderless cemented carbide, the preparation method comprising the following steps:

[0178] (a) Two metal layers are coated on the surface of the pre-sintered body; wherein the material of the innermost metal layer is nickel-iron alloy (melting point T m1 1430℃), thickness 0.3mm; the material of the outermost metal layer is titanium (melting point T m2 1668℃), thickness is 0.2mm;

[0179] The coating method of the innermost metal layer is spray coating; the coating method of the outermost metal layer is metal thin-walled parts sleeve method;

[0180] The pre-sintered body is the pre-sintered body provided in Preparation Example 6;

[0181] (b) At a pressure of 10 -3 The vacuum sintering is carried out under the condition of less than Pa, and the vacuum sintering temperature T 1 The temperature is 1430℃ and the holding time is 0.5h;

[0182] (c) Hot isostatic pressing sintering was carried out in an argon atmosphere at a pressure of 200 MPa and a temperature of T 2 The temperature is 1380℃ and the holding time is 1.5h to obtain nanocrystalline cemented carbide without binder phase.

[0183] Since the temperature of hot isostatic pressing sintering is relatively low, the relative density of the nanocrystalline binderless cemented carbide obtained in this embodiment reaches 99.89%, and the average size of the grains is 153nm. However, similar to Example 2, since the relative density of the pre-sintered body is relatively low, which is 80%, the molten liquid phase of the innermost metal layer diffuses slightly on the surface of the pre-sintered body during vacuum sintering, and therefore, the surface quality of the obtained nanocrystalline binderless cemented carbide is slightly poor.

[0184] Example 7

[0185] This embodiment provides a method for preparing a nanocrystalline binderless cemented carbide, the preparation method comprising the following steps:

[0186] (a) Two metal layers are coated on the surface of the pre-sintered body; the material of the innermost metal layer is ZrCo alloy (melting point T m1 1668℃), thickness 0.1mm; the material of the outermost metal layer is niobium (melting point T m22468℃), thickness is 0.1mm;

[0187] The coating method of the innermost metal layer is spray coating; the coating method of the outermost metal layer is metal thin-walled parts sleeve method;

[0188] The pre-sintered body is the pre-sintered body provided in Preparation Example 1;

[0189] (b) At a pressure of 10 -3 The vacuum sintering is carried out under the condition of less than Pa, and the vacuum sintering temperature T 1 The temperature is 1668℃ and the holding time is 1h;

[0190] (c) Hot isostatic pressing sintering was carried out in an argon atmosphere at a pressure of 170 MPa and a temperature of T 2 The temperature is 1640℃ and the holding time is 1.5h to obtain nanocrystalline cemented carbide without binder phase.

[0191] Example 8

[0192] This embodiment provides a method for preparing a nanocrystalline binderless cemented carbide, the preparation method comprising the following steps:

[0193] (a) Two metal layers are coated on the surface of the pre-sintered body; the material of the innermost metal layer is titanium (melting point T m1 1668℃), thickness 0.5mm; the material of the outermost metal layer is tantalum (melting point T m2 2996℃), thickness is 0.3mm;

[0194] The coating method of the innermost metal layer is spray coating; the coating method of the outermost metal layer is metal thin-walled parts sleeve method;

[0195] The pre-sintered body is the pre-sintered body provided in Preparation Example 1;

[0196] (b) At a pressure of 10 -3 The vacuum sintering is carried out under the condition of less than Pa, and the vacuum sintering temperature T 1 The temperature is 1668℃ and the holding time is 1h;

[0197] (c) Hot isostatic pressing sintering was carried out in an argon atmosphere at a pressure of 170 MPa and a temperature of T 2 The temperature is 1640℃ and the holding time is 1.5h to obtain nanocrystalline cemented carbide without binder phase.

[0198] Comparative Example 1

[0199] This comparative example provides a method for preparing nanocrystalline cemented carbide without a binder phase, except that the vacuum sintering temperature T 1 Except for the temperature being 1700°C, the rest is the same as Example 1-1.

[0200] Since the temperature of vacuum sintering is much higher than the melting point of the innermost titanium metal layer, on the one hand, the diffusion capacity of the molten metal liquid phase increases rapidly, resulting in an increase in the depth of its diffusion along the pores into the pre-sintered body, and the surface quality of the obtained binderless cemented carbide decreases; on the other hand, the increase in the temperature of vacuum sintering leads to grain growth, and the average grain size of the final binderless cemented carbide reaches 213nm.

[0201] Comparative Example 2

[0202] This comparative example provides a method for preparing a nanocrystalline binderless cemented carbide. Except that the pre-sintered body is the pre-sintered body provided in comparative preparation example 1, the rest is the same as that of embodiment 1-1.

[0203] The average grain size of the nanocrystalline cemented carbide without binder phase obtained in this comparative example is 286nm, and its fracture morphology is as follows: Figure 3 As shown, the grain morphology of the polished and corroded surface is shown in Figure 4 shown.

[0204] Comparative Example 3

[0205] This comparative example provides a method for preparing a nanocrystalline binderless cemented carbide. Except that the pre-sintered body is the pre-sintered body provided in comparative preparation example 2, the rest is the same as that of embodiment 1-1.

[0206] Since the relative density of the pre-sintered body of this comparative example is relatively low, at 63%, it is all open pores. On the one hand, the strength of the pre-sintered body is also relatively low, and it is easy to cause damage to its edges and corners when the pre-sintered body is further operated and processed. On the other hand, when vacuum sintering, the molten metal liquid phase diffuses too deeply into the interior of the pre-sintered body along the pores, causing the material of the cemented carbide without a binder phase to change, and it cannot meet the application requirements of molds, cutting tools or wear-resistant parts.

[0207] Comparative Example 4

[0208] This comparative example provides a method for preparing a binder-free cemented carbide, which is the same as Example 5 except that only a cobalt layer with a thickness of 0.3 mm is coated on the surface of the pre-sintered body, that is, the outermost molybdenum metal layer is omitted.

[0209] In this comparative example, since only one cobalt layer is coated, during vacuum sintering, the molten cobalt liquid flows to the lower part of the product under the action of gravity, resulting in the upper part of the product not being well sealed. After subsequent hot isostatic pressing sintering, the product cannot be sintered densely.

[0210] Comparative Example 5

[0211] This comparative example provides a method for preparing a binderless cemented carbide, which is the same as Example 1-1 except that only a molybdenum layer with a thickness of 0.3 mm is coated on the surface of the pre-sintered body, that is, the innermost titanium metal layer is omitted.

[0212] In this comparative example, since only one metal molybdenum layer is coated, during vacuum sintering and hot isostatic pressing, the sintering temperature is lower than the melting point of the molybdenum layer, so it always remains solid and the pre-sintered body cannot be sealed by melt sealing, resulting in the inability to sinter the product densely.

[0213] Comparative Example 6

[0214] This comparative example provides a method for preparing nanocrystalline cemented carbide without a binder phase, except that the temperature T 2 Except for the temperature being 1668°C, the rest are the same as those in Example 1-1.

[0215] Compared with Example 1-1, since the temperature of hot isostatic pressing sintering in this comparative example is increased to reach the melting point of the innermost metal layer, the innermost metal layer does not remain in a solid state during hot isostatic pressing sintering, but melts. Under the action of pressure, the molten liquid phase rapidly diffuses into the interior along the pores of the pre-sintered body, resulting in an increase in the titanium metal content in the organizational structure of the binderless cemented carbide obtained after sintering at a certain depth from the surface. Within this depth range, the performance of the binderless cemented carbide is sharply reduced, and the application requirements of molds, cutting tools or wear-resistant parts cannot be met.

[0216] The average grain size and relative density of the cemented carbides obtained in the above examples and comparative examples are shown in Table 2 and Table 3, wherein the average grain size is measured by scanning electron microscopy (SEM), and the relative density is measured by Archimedes drainage method. The relative density of the obtained cemented carbide refers to the ratio of the density of the obtained cemented carbide to the theoretical density.

[0217] Table 2. Experimental parameters of various embodiments and comparative examples

[0218]

[0219]

[0220] Table 3. Test results of various embodiments and comparative examples

[0221]

[0222]

[0223] In summary, the present invention realizes the sintering of binderless cemented carbide at a relatively low temperature by coating at least two metal layers on the surface of the pre-sintered body, thereby solving the contradiction between higher temperature promoting sintering densification but causing grain growth and lower temperature inhibiting grain growth but sintering not being dense, and finally a nanocrystalline binderless cemented carbide with an average grain size of less than 200nm and a relative density of more than 99.8% can be obtained; in addition, vacuum sintering and hot isostatic pressing sintering are not limited by product shape and can realize mass production; the nanocrystalline binderless cemented carbide prepared by the present invention has an average grain size of less than 200nm and a relative density of more than 99.8%.

[0224] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing nanocrystalline cemented carbide without a binder phase, characterized in that: The preparation method comprises the following steps: Coating at least two metal layers on the surface of the pre-sintered body, and then sequentially performing vacuum sintering and hot isostatic pressing sintering to obtain the nanocrystalline binder-free cemented carbide; The relative density of the pre-sintered body is 80% to 92%, and the average grain size of the pre-sintered body is less than 150nm; The melting point of the outermost metal layer of the at least two metal layers is T m2 Higher than the melting point T of the innermost metal layer m1 and the vacuum sintering temperature T1; The melting point of the innermost metal layer is T m1 0°C to 20°C lower than the vacuum sintering temperature T1; In the at least two metal layers, the melting point of each metal layer is higher than the hot isostatic pressing sintering temperature T2.

2. The preparation method according to claim 1, characterized in that: The melting point of the innermost metal layer is T m1 1430℃ to 1820℃; Preferably, the material of the innermost metal layer includes any one or a combination of at least two of Ni, Co, Fe or Ti, or a combination of Zr and at least one of Ni, Co, Fe or Ti; Preferably, the material of the outermost metal layer includes any one of Ti, Zr, Mo, Nb or Ta, or a combination of at least two of them.

3. The preparation method according to claim 1 or 2, characterized in that: The thickness of the innermost metal layer is 0.1 mm to 0.5 mm; Preferably, the thickness of the outermost metal layer is 0.1 mm to 0.3 mm.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The vacuum sintering is carried out in a high vacuum; Preferably, the vacuum sintering temperature T1 is 1430°C to 1840°C; Preferably, the holding time of the vacuum sintering is 0.5h to 1h; Preferably, the vacuum sintering pressure is 10 -3 Below Pa.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The hot isostatic pressing sintering is carried out in an inert atmosphere; Preferably, the hot isostatic pressing sintering pressure is 150 MPa to 300 MPa; Preferably, the hot isostatic pressing sintering temperature T2 is higher than the melting point T m1 Low 10℃ to 50℃; Preferably, the hot isostatic pressing sintering temperature T2 is 1380° C. to 1810° C.; Preferably, the holding time of the hot isostatic pressing sintering is 1 h to 3 h.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method of the pre-sintered body comprises powder mixing, molding, degreasing and vacuum pre-sintering in sequence; Preferably, the vacuum pre-sintering temperature T3 is 1450°C to 1870°C; Preferably, the holding time of the vacuum pre-sintering is 1h to 3h; Preferably, the vacuum pre-sintering pressure is below 30 Pa.

7. The preparation method according to any one of claims 1 to 6, characterized in that: Measured in percentage by mass, the composition of the nanocrystalline binder-free cemented carbide includes: more than 91wt% of WC, less than 1wt% of binder metal and the remainder of additives.

8. The preparation method according to claim 7, characterized in that: The bonding phase metal includes any one of Co, Ni or Fe or a combination of at least two thereof; Preferably, the additive includes any one of Cr3C2, VC, ZrC, TiC, Mo2C, TaC, NbC, SiC, B4C, ZrB, ZrB2, TiB, TiB2, WB, W2B, W2B5, CrB, AlN, ZrN, TiN, TiCN, Si3N4, BN or rare earth metals, or a combination of at least two thereof.

9. A nanocrystalline binderless cemented carbide, characterized in that: The nanocrystalline binder-free cemented carbide is prepared by the preparation method according to any one of claims 1 to 8; The average grain size of the nanocrystalline binder-free hard alloy is less than 200 nm, and the relative density is higher than 99.8%.

10. An application of nanocrystalline cemented carbide without a binder phase, characterized in that: The nanocrystalline binder-free hard alloy is used for preparing molds, cutting tools or wear-resistant parts; The nanocrystalline binder-free cemented carbide is prepared by the preparation method described in any one of claims 1 to 8, or is the nanocrystalline binder-free cemented carbide described in claim 9.

Citation Information

Patent Citations

  • Preparation method of binderless nanometer tungsten carbide cemented carbide

    CN102925728A

  • Method for preparing nanostructure tungsten carbide composite bulk by high temperature and ultra high pressure

    CN103667845A

  • Method for preparing tungsten carbide ceramic material

    CN107522490A

  • SPS sintering method of a large-size non-bonding-phase pure tungsten carbide hard alloy

    CN108165859A

  • Large-size high-density non-binding-phase tungsten carbide target material and preparing method thereof

    CN110171975A